2019
DOI: 10.1002/anie.201904795
|View full text |Cite
|
Sign up to set email alerts
|

The Buchwald–Hartwig Amination After 25 Years

Abstract: The Pd‐catalyzed coupling of aryl (pseudo)halides and amines is one of the most powerful approaches for the formation of C(sp2)−N bonds. The pioneering reports from Migita and subsequently Buchwald and Hartwig on the coupling of aminostannanes and aryl bromides rapidly evolved into general and practical tin‐free protocols with broad substrate scope, which led to the establishment of what is now known as the Buchwald–Hartwig amination. This Minireview summarizes the evolution of this cross‐coupling reaction ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
274
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(279 citation statements)
references
References 192 publications
3
274
0
2
Order By: Relevance
“…[23] Between these two extremes, bulky dialkyl biarylphosphine ligands introduced by Buchwald in 1998 for Pdcatalyzed coupling reactions, [25] provide electronically and sterically an intermediate alternative. Due to their stability with respect to oxidation [26] and synthetic accessibility, [27] this class of ligands has been employed in numerous Pd-catalyzed CÀ C [28,29] and CÀ X (X=N, O, F) [30][31][32][33] bond-forming reactions as well as in combination with other transition metals such as Ag, [34] Rh, [35,36] Ru [37] and Cu. [38] Our group introduced the use of dialkyl biarylphosphine ligands in the context of gold(I) catalysis [39] resulting in a new family of highly electrophilic gold(I) complexes A-D which were found to catalyze diverse transformations upon chloride abstraction.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Between these two extremes, bulky dialkyl biarylphosphine ligands introduced by Buchwald in 1998 for Pdcatalyzed coupling reactions, [25] provide electronically and sterically an intermediate alternative. Due to their stability with respect to oxidation [26] and synthetic accessibility, [27] this class of ligands has been employed in numerous Pd-catalyzed CÀ C [28,29] and CÀ X (X=N, O, F) [30][31][32][33] bond-forming reactions as well as in combination with other transition metals such as Ag, [34] Rh, [35,36] Ru [37] and Cu. [38] Our group introduced the use of dialkyl biarylphosphine ligands in the context of gold(I) catalysis [39] resulting in a new family of highly electrophilic gold(I) complexes A-D which were found to catalyze diverse transformations upon chloride abstraction.…”
Section: Introductionmentioning
confidence: 99%
“…By expending the time and effort to understand the fundamental processes that form the basis of the catalytic systems that facilitated CÀ N coupling, we and others have been able to develop new and improved catalysts. [30][31][32][33][34][35][36] These catalysts, in turn, have greatly increased the range of substrates and applications that are suitable for the methodology that has been developed.…”
mentioning
confidence: 99%
“…An increase in the bulkiness of the substituents at the bromine atom in isomeric 1-bromo-2-fluoro-3-(trifluoromethyl)benzene and 2-bromo-1-fluoro-4-(trifluoromethyl)benzene led to insignificant decrease in the yields of corresponding derivatives 22 and 23 (entries 9 and 10). The introduction of more sterically hindered compounds in which the trifluoromethyl group is in the ortho-position to bromine demanded an increase of the catalyst to 8 mol% and the products 24-26 were obtained in low yields (entries [11][12][13]. The analysis of the reaction mixtures by 1 H NMR showed that many side processes other than amination took place in these cases (see also Supplementary Information, Scheme S2, Tables S3 and S4).…”
Section: Catalytic Amination Of Halogeno(trifluoromethyl)benzenesmentioning
confidence: 99%
“…This reinforces the importance of studies on convenient synthetic routes to these compounds, among which, the catalytic amination of corresponding halogenosubstituted fluorinated (hetero)aromatic compounds can be regarded as most straightforward and versatile procedure. Palladium-catalyzed amination of (hetero)aryl halides is well-known and widely described in the literature [9][10][11]. During last decade, an important trend in the catalytic organic synthesis has been clearly exhibited, that is, the so-called renaissance of Ullmann chemistry, which is extremely important for the development of new strategies of C-N bond formation [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%